The diagnostic value of the olfactory evaluation for congenital hypogonadotropic hypogonadism - Yu, Bingqing; Chen, Kepu; Mao, Jiangfeng; Hou, Bo; You, Hui; Wang, Xi; Nie, Min; Huang, Qibin; Zhang, Rui; Zhu, Yiyi; Sun, Bang; Feng, Feng; et al. (Frontiers in Endocrinology, 2022)
Objective To evaluate the diagnostic accuracy of different olfactory evaluation tools in congenital hypogonadotropic hypogonadism (CHH) patients. Methods Seventy-one CHH patients were prospectively recruited at Peking Union Medical College Hospital between November 2020 and July 2021. The Chinese Olfactory Function Test (COFT) and self-reported olfactory scale (SROS) were adapted as the subjective tools for evaluation of olfactory function and magnetic resonance imaging of olfactory apparatus (MRI-OA) was the objective tool. The olfactory bulb volume (OBV) and the olfactory sulcus depth (OSD) were quantified. Results Based on the COFT, 36 patients were assigned as normosmic CHH (nCHH), and the other 35 patients were Kallmann syndrome (KS). Among nCHH patients, 35 patients were grouped into normal olfaction and 1 patient was abnormal olfaction by SROS. For KS patients, there were 30 patients grouped into abnormal olfaction, while 5 paitents were normal by SROS. For MRI-OA, 67% (18/27) nCHH patients showed normal olfactory apparatus, 33% (9/27) showed bilateral or unilateral olfactory bulb aplasia or hypoplasia. Among KS patients, 96% (27/28) patients showed bilateral olfactory bulb hypoplasia or aplasia, and 4% (1/28) patients showed normal olfactory apparatus. All 6 patients with UOA and 3 patients with BOA dysplasia showed normal olfactory function. The accuracy of the SROS in the diagnosis nCHH and KS was 91.5% with a sensitivity of 0.857 and a specificity of 0.972, while the accuracy of MRI-OA is 92.7%, with a sensitivity of 0.964 and a specificity of 0.889. Conclusion SROS and MRI-OA both showed high accuracy to distinguish between KS and nCHH. Abnormal structure of the olfactory apparatus was relatively common in nCHH patients. CHH patients with UOA dysplasia usually had normal olfaction. Normal olfaction without apparent olfactory bulbs is rare but occurred in male CHH patients.